Survival and Growth Improvement of Palm Ruff, Seriolella Violacea, Larvae Fed Artemia Nauplii Enriched with an Experimental Emulsion - Martinez-Fernandez, C; Gonzalez-Chia, A (Blackwell Publishing Inc., 2017)
The palm ruff, Seriolella violacea (Cojinoba), is a potential new species for Chilean aquaculture. To approach Cojinoba larviculture, an experimental Artemia enrichment emulsion, containing docosahexaenoic acid (DHA)/eicosapentaenoic acid (EPA) = 2.5, supplemented with vitamin E, astaxanthin, and β-glucan, was evaluated in both Artemia and Cojinoba larvae, 30–50 d.a.h. This study tested an experimental enrichment emulsion versus a commercial emulsion, with an integral approach of multicompound emulsions. After 23 h enrichment, experimental emulsion (EE)-enriched nauplii reached DHA and EPA concentrations of 23.8 and 18.7 mg/g dry weight (dwt), respectively, while in Cojinoba larvae they were 18.4 and 19.7 mg/g dwt. Control emulsion (CE)-enriched nauplii exhibited lower DHA and EPA (6.1 and 7.7 mg/g dwt), while only DHA decreased in the control larvae (12.6 mg/g dwt). Vitamin E was higher in EE-enriched nauplii (29.2 mg/100 g dwt) than in the control (8.4 mg/100 g dwt). Larvae fed EE-enriched Artemia exhibited 8% increase in survival and 19% in growth compared with the control. Astaxanthin was detected only in larvae fed EE-enriched nauplii. The tumor necrosis factor-α concentration was not significantly different between larvae fed EE- and CE-enriched nauplii. EE looks promising as an Artemia enrichment and experimental diet to assess palm ruff larval requirements, and has a positive impact on fish larvae performance. © Copyright by the World Aquaculture Society 2016